Dynamics of two mutually delay-coupled semiconductor lasers - Rogister, F.; Blondel, M. (Optics communications, 2004)
We investigate numerically the dynamics of two semiconductor lasers mutually coupled via their optical fields in the particular case of a small separation between them. We show that, depending on the frequency detuning and the coupling between the lasers, the system shares the main features of semiconductor lasers subject either to constant monochromatic optical injection or to optical feedback from a distant reflector.